Productive technologies versus marketing channels for vegetables (Desenvolvimento em Questão, 2024)
This research, in addition to characterizing vegetable producing establishments, investigated the adoption of technologies in vegetable production by family farmers and the relationship with marketing channels. The research involved mixed methods, quantitative and qualitative, data were collected in person in 2023 directly in rural establishments through a questionnaire with the owners of 30 agricultural establishments producing vegetables in the three largest municipalities (by population) in the Region Central Rio Grande do Sul, Brazil (Cachoeira do Sul; Santiago and Santa Maria). Data analysis used descriptive statistics, non-parametric statistical tests and the Chi-Square test, using the SPSS@ software. An aging trend, masculinization of the rural population and the predominance of establishments of up to 10 hectares were identified. The positive correlations with the fair sales channel were: 1) Knowledge technology (technical assistance); 2) Fertilization technology and phytosanitary control (organic fertilizer and alternative management); 3) Irrigation technology (manual system); 4) Traction technology and equipment (motor cultivators and rotary hoes). The supermarket channel correlated with: 1) Fertilization technology and phytosanitary control (chemical fertilization and conventional management); 2) Irrigation technology (drip); 3) Coverage and crop protection technologies (plastic/greenhouse). The data from this study can help develop public policies, as by encouraging a certain technology, one or another sales channel can be boosted.
Keywords: Supermarkets; Technical assistance; Organic fertilization; Irrigation